1995
DOI: 10.1128/aem.61.8.3002-3007.1995
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Disruption of the Biosynthesis Genes Coding for the Antifungal Metabolite 2,4-Diacetylphloroglucinol Does Not Influence the Ecological Fitness of Pseudomonas fluorescens F113 in the Rhizosphere of Sugarbeets

Abstract: The ability of Pseudomonas fluorescens F113 to produce the antibiotic 2,4-diacetylphloroglucinol (DAPG) is a key factor in the biocontrol of the phytopathogenic fungus Pythium ultimum by this strain. In this study, a DAPG-producing strain (rifampin-resistant mutant F113Rif) was compared with a nearly isogenic DAPG-negative biosynthesis mutant (Tn5::lacZY derivative F113G22) in terms of the ability to colonize and persist in the rhizosphere of sugarbeets in soil microcosms during 10 plant growth-harvest cycles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Pythium ultimum causes dampingoff of pea seedlings, and the Phl-producing strains inhibit Pythium growth in plate assays (Fenton et al 1992). Deletion of the biosynthetic locus for Phl production showed that the ability to produce Phl in strain F113 was responsible for the biocontrol properties of this strain, but did not contribute to its rhizosphere competence (Fenton et al 1992;Carroll et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Pythium ultimum causes dampingoff of pea seedlings, and the Phl-producing strains inhibit Pythium growth in plate assays (Fenton et al 1992). Deletion of the biosynthetic locus for Phl production showed that the ability to produce Phl in strain F113 was responsible for the biocontrol properties of this strain, but did not contribute to its rhizosphere competence (Fenton et al 1992;Carroll et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that successful root colonization is an important prerequisite for effective biocontrol (Weller, 1988;Bull et al, 1991). Biocontrol agents introduced as soil or seed inoculants colonize the root system in competition with the indigenous soil microbiota (Weller, 1988;Parke, 1990;Weller & Thomashow, 1994;Carroll et al, 1995). Strains of the Pseudomonas fluorescens-putida group are often aggressive root-colonizers and can constitute half or more of the total number of culturable rhizosphere bacteria following their introduction into the rhizosphere (Bowen & Rovira, 1976;Smiley, 1979;Schroth & Hancock, 1982;Carroll et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Introduced rhizobacteria tend to colonize primarily the older parts of the root and consequently are found at comparatively lower numbers in the root tip area (Russo et al, 1996). Often, the population size of biocontrol inoculants has been monitored by colony counts, at the scale of the whole root system (Natsch et al, 1994;Carroll et al, 1995) or particular root segments (Bull et al, 1991;Russo et al, 1996). However, these determinations do not yield any information on the distribution of individual cells of the inoculant in the rhizosphere and their physical interaction with the target fungal pathogen, which are poorly understood (Fukui et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…For strains such as Pseudomonas fluorescens 2-79 and P. aureofaciens 30-84, the production of phenazine antibiotics contributes to competitiveness on the roots of wheat (Mazzola et al 1992). In contrast, for P. fluorescens F113, the production of the antibiotic 2,4-diacetylphloroglucinol does not appear to be a factor in the competitiveness of the strain on the roots of sugarbeet (Carroll et al 1995). Metabolites that directly suppress plant-pathogenic fungi could also have some other function, such as serving as a siderophore for the uptake of iron.…”
Section: Special Featurementioning
confidence: 98%
“…These tools include isogenic mutants of rhizobia whose altered symbiotic function is linked to alteration of a single gene (Tirichine et al 2000). Fine-structure genetic analyses (Raaijmakers and Weller 2001) and genetic modification (Carroll et al 1995) of Pseudomonas fluorescens also are providing insights into its ecological role.…”
Section: New Research Toolsmentioning
confidence: 99%